TINGKAT PENGUNGKAPAN INFORMASI KEUANGAN DAN NONKEUANGAN MELALUI WEBSITE PERBANKAN DI INDONESIA - Adi, Bagas Prasetyo; Rahardjo, Shiddiq Nur (Diponegoro Journal of Accounting, 2012)
Disclosure is a tool that can be used by management to improve corporate image. Management may disclose financial and non–financial information via the website, which is one form of the practice of Internet Financial Reporting (IFR). The higher level of disclosure made ​​by the company, it shows a positive signal to distinguish between companies with one another in attracting investors. This study is a quantitative study using secondary data. Number of samples used were as many as 74 banks are divided into a bank asing, bank campuran, bank BUMN (Persero), bank umum swasta nasional (BUSN) devisa, bank umum swasta nasional (BUSN) non devisa, and bank pembangunan daerah (BPD). Method of processing data using SPSS version 17.0 through multiple linear regression. The results of hypothesis test showed that only the size of banks and banking listing status is significantly and positively influence the level of disclosure of financial and non financial information via the website of Indonesian banks.